A Novel Mutation of the Calcium Sensing Receptor Gene in a Franconian Kindred: Heterozygous Mutation c.1697_1698delTG Exon 6 - Cordes, M.; Kuwert, T.; Haag, C.; Raue, F. (Hormone and Metabolic Research, 2017)
Familial hypocalciuric hypercalcemia (FHH) belongs to the disorders of a disturbed calcium homeostasis. Genetically, the disorder is inherited in an autosomal-dominant trait and represents an inactivating mutation of the calcium sensing receptor (CaSR) gene. We identified a Franconian kindred in which 6 individuals could be tested by molecular genetic means. In 5 individuals of 3 generations, the mutation could be classified as c.1697_1698delTG. This novel germline mutation creates a premature stop codon leading to a loss of 510 amino acids of the protein. The detection of CaSR gene mutations is suitable to differentiate states of hypercalcemia and may help to avoid invasive procedures such as parathyroidectomies.
Keywords: calcium sensing receptor; inactivating gene mutations; hypercalcemia; familial hypocalciuric hypercalcemia